Arsitektur Software Defined Network: Implementasi Pada Small Network - Intraswadaya Hidayat; Bima Abdi Perdana (Institute of Information Technology and Social Science (IITSS), 2020)
Software Defined Network and Openflow protocols are currently growing rapidly. But its use in small networks and home offices is still very rare. This article discusses the use of Software Defined Network architecture in small and home office networks so that it can be developed so that the SDN architecture can be an alternative in network development that requires complex network management but is limited by the cost of infrastructure development.